Whole Blood Metabolomic Profiling of Mice with Tacrolimus-Induced Chronic Nephrotoxicity: NAD+ Depletion with Salvage Pathway Impairment - Sho Nishida; Tamaki Ishima; Daiki Iwami; Ryozo Nagai; Kenichi Aizawa (Antioxidants)
Tacrolimus (TAC)-induced chronic nephrotoxicity (TAC nephrotoxicity) is a serious issue for long-term graft survival in kidney transplantation. However, the pathophysiology of TAC nephrotoxicity remains unclear. In this study, we analyzed whole blood samples from mice that developed TAC nephrotoxicity in order to discover its mechanism. Mice were divided into a TAC group and a control group (n = 5 per group). The TAC group received TAC subcutaneously (1 mg/kg/day for 28 days), while the control group received normal saline instead. After the administration period, whole blood was collected and metabolomic analysis was performed, revealing significant changes in 56 metabolites. The major metabolic changes were related to uremic toxins, vascular damage, and NAD+. NAD+ levels were significantly lower in the TAC group, and ADP-ribose, nicotinamide, and nicotinamide N-oxide, which are degradation products of NAD+, were significantly higher, suggesting impairment of the NAD+ salvage pathway. NAD+ deficiency suggests cellular aging and mitochondrial dysfunction, which may induce vascular damage and chronic kidney disease. Our study demonstrated a correlation between low NAD+ levels and the pathophysiology of TAC nephrotoxicity.